The Influence of Halal Lebel and Product Quality on Drug Purchase Interest - Lubis, Nurul Rafiqoh; Balqis, Tsamara; Batubara, Chuzaimah (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2023)
This research explores the influence of halal labels and product quality on the purchase intention of medicines, with a focus on postgraduate Sharia Economics students at the State Islamic University of North Sumatra (UINSU). In the context of Indonesia, with its significant Muslim-majority population, halal products have substantial growth potential. However, consumer awareness of the halal status of non-food products, particularly in the pharmaceutical sector directly impacting public health, remains low. The study aims to examine two independent variables: the influence of halal labels and product quality on the purchase intention of medicines. The hypotheses suggest that both halal labels and product quality have a significant influence on the purchase intention of medicines. A quantitative research method is employed, with data collected through a survey questionnaire distributed to postgraduate students in Sharia Economics at UINSU. The findings of this research are expected to provide insights into the factors affecting consumer decisions when purchasing halal medicines. Furthermore, the study's results may have practical implications for businesses and policymakers interested in promoting the production and consumption of halal products in Indonesia. This research is particularly relevant given Indonesia's status as the world's largest halal industry market.